(untitled) (Al-Mansour Journal, 2022)
This research tries to shed light on the problem of application of electronic management and availability requirements necessary in colleges and institutes of technical education / complex Zafaraniyah for this purpose form was designed questionnaire was distributed to members of the research sample totaling (34) people , has been used statistical program(spss) to analyze the data and methods used statistical quantity as well s the experimental co analysis and simple regression to know the effect of independent variables on the dependent variable, as well as multiple regression to determine any requirement more influential in changing the approved and came out research group conclusions of the most important despite the fact that there are signs of the development of IT infrastructure in Iraq , but the benefit Almazmat educational research sample of that progress does not rise to the aspirations desired as well as the slowness to keep pace with the information revolution , and also provided a set of recommendations , the most important interest in the establishment of infrastructure new communication and information within colleges , institutes and caliber of human excellence in the field of electronic management of trainers , consultants and experts in the design and develop programs to take advantage of their expertise.